Faith No More Why People Reject Religion by Phil Zuckerman (New York: Oxford University Press, 2012), 224 pages, ISBN: 9780199740017 - Nafiye Aydın (Atebe)
This study evaluates the book “Faith No More Why People Reject Religion” written by Phil Zuckerman. Zuckerman, who conducts research in the fields of atheism, agnosticism, skepticism, humanism, and naturalism, examines the intellectual and social characteristics of people who abandon their beliefs in his book “Faith No More Why People Reject Religion” and questions whether people need a God to be truly moral. In our study, the apostasy stories in the book have been examined by comparing them with the author’s theses. Relationships between apostasy rates and given social variables have been evaluated in terms of scientific objectivity.